ANALISIS KETERLAMBATAN PROYEK PENINGKATAN JALAN KREMBUNG-MOJORUNTUT KABUPATEN SIDOARJO - Masliyah, Masliyah; Saraswati, Nina; Firmansyah, Mohammad Afif Ardian (Rang Teknik Journal, 2026)
Delays are a frequent challenge in construction projects, often arising from a combination of internal and external factors. This study focuses on analyzing delays in the Krembung–Mojoruntut Road Improvement Project in Sidoarjo Regency. A quantitative approach was adopted, utilizing the Earned Value Management (EVM) method to assess both cost and time performance. Data were collected from contract documents, S-curves, daily reports, and weekly progress updates spanning 27 weeks of project implementation. The analysis centered on three key indicators: Budgeted Cost of Work Scheduled (BCWS), Budgeted Cost of Work Performed (BCWP), and Actual Cost of Work Performed (ACWP). The findings reveal that the project experienced delays almost every week, with varying degrees of deviation, necessitating two schedule addendums. In the 26th week, the Schedule Performance Index (SPI) was 0.96, indicating a slight lag behind schedule, while the Cost Performance Index (CPI) was 1.05, showing that the project remained cost-efficient. The estimated total cost at completion (Estimate at Completion/EAC) was Rp10,067,384,650.67, slightly below the original contract value, while the estimated completion time (Estimate at Schedule/EAS) aligned with the revised target, thanks to the additional time granted through the addendums. Key factors contributing to the delays included late material procurement, adverse weather conditions, and less-than-optimal workforce management (Kharina Sambowo; Mahapatni Putra, 2022).Keywords: Project Delay, Estimate At Completion, Estimate At Schedule